Live-in "strangers": An experiential account of gerontology educational immersion in senior housing. Issue 1 (2nd January 2018) - Kilaberia, Rusudan; Ratner, Edward
ABSTRACT: Gerontology education programs that combine elements of experiential service-learning, community participation, and residential immersion have been emerging in the United States and internationally. Combining fieldwork, interviews, and immersion methods, this study draws on qualitative ethnographic and phenomenologic design, whereby a student lived in senior housing for 3.5 years. The study is among the longest and most intensive gerontological field experiences ever reported. It is based on more than 2, 000 hours of observations and conversational interviews with 14 residents. Major patterns based on observational data show the importance of shared history, support for one another, negotiating environmental tensions, and demand for attention on the part of residents. Major themes derived from interviews elaborate on family conflict, conflict between residents, and life decisions. Results show that a unique combination of physical and social proximity in an intergenerational alliance enables life enhancement for older adults and learning opportunities for students. A recommendation is made to implement a live-in role more formally.